2018
DOI: 10.1016/j.yhbeh.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Saliva oxytocin measures do not reflect peripheral plasma concentrations after intranasal oxytocin administration in men

Abstract: Oxytocin plays an important role in social behavior. Thus, there has been significant research interest for the role of the oxytocin system in several psychiatric disorders, and the potential of intranasal oxytocin administration to treat social dysfunction. Measurement of oxytocin concentrations in saliva are sometimes used to approximate peripheral levels of oxytocin; however, the validity of this approach is unclear. In this study, saliva and plasma oxytocin was assessed after two doses of Exhalation Delive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…The lack of increase in salivary oxytocin after the intravenous administration of exogenous oxytocin that was consistently found in our study and in a previous study ( Quintana et al, 2018 ) also raises the question of how oxytocin reaches the saliva if not from the blood. Currently, there is no evidence of direct acinar secretion or direct nerve terminals release of oxytocin to the saliva; therefore, transport from the blood remains as the most plausible mechanism of appearance of oxytocin in the saliva.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of increase in salivary oxytocin after the intravenous administration of exogenous oxytocin that was consistently found in our study and in a previous study ( Quintana et al, 2018 ) also raises the question of how oxytocin reaches the saliva if not from the blood. Currently, there is no evidence of direct acinar secretion or direct nerve terminals release of oxytocin to the saliva; therefore, transport from the blood remains as the most plausible mechanism of appearance of oxytocin in the saliva.…”
Section: Discussionsupporting
confidence: 89%
“…We could replicate previous evidence that intravenous oxytocin does not increase salivary oxytocin ( Quintana et al, 2018 ) and extended it by showing that the lack of increase in salivary oxytocin is not limited to the specific low dose of intravenous OT that was previously used (1IU) and that it is not driven by the insufficient sensitivity of the OT measurement method which had resulted in more than 50% of the saliva samples being discarded in the previous study ( Quintana et al, 2018 ). Therefore, our data supports the notion that increases in salivary oxytocin after its intranasal administration most likely reflect drip-down oxytocin from the nasal cavity ( Quintana et al, 2018 ). If this is the case then oxytocin elevations in saliva are mainly driven by non-absorbed exogenous oxytocin and therefore their use to estimate levels of systemic absorption or predict treatment effects after intranasal oxytocin administration is not valid.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In humans, oxytocin reaches the salivary glands via blood circulation through active transport mechanisms [31]. However, the dynamic of oxytocin in both fluids (blood and saliva) could be different, since saliva concentrations of oxytocin do not reflect peripherally circulating oxytocin after exogenous administration in humans [32]. Martin et al [33] found that oxytocin concentrations in human saliva are more correlated with those in cerebrospinal fluid, and therefore with central oxytocin, than with those of blood plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed reliable variations in oxytocin concentration, especially in rapid response to specific experiences, such as anticipation of breast feeding ( White-Traut et al, 2009 ), sexual stimulation, exercise, affiliative social contact, and psychologic stress ( Jong et al, 2015 ; MacLean et al, 2017a ). However, the relationships between concentrations of peptides in saliva, blood, and peptide concentrations in the source brain nuclei are not yet well-understood ( Quintana et al, 2018 ).…”
Section: Measurement Of Oxytocinmentioning
confidence: 99%